Kajian Potensi Airtanah Untuk Kebutuhan Domestik Air Masyarakat di Kecamatan Mantrijeron, Kota Yogyakarta - Paramita, Sekar Langit Adesya; , Drs. H. Yuli Priyana M.Si (2017)
The problem about fresh water has become a familiar case in the large city. Recently many isues about critical fresh water in Yogyakarta become topic in various media. Mantrijeron Subdistrict is one of subdistrict that mentioned as water crisis areas. This research aim are to find out the potency of fresh water in Mantrijeron Subdistric (1), the sum of fresh water domestic need (2) and to forecast the sum of fresh water domestic need in the future (3). The potency of fresh water be calculated by static method, the sum of fresh water domestic need is know by the survei, and projection of the water domestic need in the future is approached by total population on that year. Descriptive and spatial analysis are used as analysis technique. The quantity potency of fresh water in Mantijeron Subdistrict as much 11.691.228,78 m3. Amount of fresh water domestic need as much 4.033.040,3 m3/year. The balance value of groundwater showing that the value was surplus 7.658.188,4 m3, but the shots of groundwater more than its save yield. Projection of the water domestic need in 2030 was increase about 180% as much 7.263.281,7 m3/year. Based on the result we have to evaluated about the pattern of groundwater using so that are not causes decreasing water level.